Synthesis and tribological behavior of novel wear-resistant PEEK–Ti3SiC2 composites. (March 2017) - Ghosh, S; Dunnigan, R; Gupta, S
In this article, the authors report the synthesis and tribological behavior of Ti3 SiC2 –PEEK composites during dry sliding. These composites were designed by adding 5 vol.% (PEEK–5%312Si), 10 vol.% (PEEK–10%312Si), 20 vol.% (PEEK–20%312Si), and 30 vol.% Ti3 SiC2 (PEEK–30%312Si) particulates in the PEEK matrix. Tab-on-disc method was used to study the tribological behavior of these samples during self-mating. As the Ti3 SiC2 content in PEEK was increased from 0 to 30 vol.%, the µmean decreased from ∼0.19 to ∼0.14 in PEEK–10%312Si, thereafter, it increased to ∼0.21 in PEEK–20%312Si and PEEK–30%312Si, respectively. The addition of Ti3 SiC2 particulates had a huge on impact on the wear resistance, e.g. PEEK–5%312Si was 27 times more wear resistant than the PEEK. It is hypothesized that the presence of Ti3 SiC2 particulates lubricated the tribocontact areas and assisted in the formation of Type IIIa lubricious tribofilms.